Going horizontal: shifts in funding of global health interventions - Bärnighausen, Till; Bloom, David E.; Humair, Salal (The New England journal of medicine, 2011)
Despite the success of recent vertical (disease-specific) interventions in global health, key organizations have begun to invest in more horizontal approaches for protecting and promoting health. But no single intervention structure is well suited to all contexts.